Algae pyrolytic poly-generation: Influence of component difference and temperature on products characteristics. (15th July 2017) - Chen, Wei; Yang, Haiping; Chen, Yingquan; Xia, Mingwei; Yang, Zixu; Wang, Xianhua; Chen, Hanping
Abstract: Pyrolytic poly-generation of three algae (Enteromorpha prolifera (EP), Spirulina platensis (SP) and Nannochloropsis sp. (NS)) was carried out in a fixed bed reactor and pyrolysis mechanism was explored in detail. Influences of pyrolysis temperature (400–800 °C) and biochemical components (carbohydrates, proteins and lipids) of algae on pyrolytic behavior and products characteristics were investigated. EP showed higher char yield, while SP and NS showed high bio-oil yields. At lower temperature (400–500 °C), CO2 was the main gas product, while H2, CH4 and CO evolved out quickly with temperature increasing. EP cracking could release more CO, while SP and NS cracking could release more H2, CH4 and C2 . While for bio-oil, it was variant with algae composition and temperature, as EP showed higher furans, SP yielded large amounts of N-containing chemicals, while aliphatics and carboxylic acids were the dominated components for NS. However, aromatics gradually became the major compounds for all bio-oil at 700–800 °C. For char, C-O/C-O-C/C=N, C=O/C-N and COO- groups cracking gradually with temperature increasing and resulted in more aromatic C=C. The optimum operating temperature is 500–600 °C for algae pyrolytic poly-generation to achieve higher value of char, bio-oil and gas products together. Highlights: Influence of component difference on algae pyrolysis products were investigated. Enteromorpha prolifera (high carbohydrates) generated 42% furans. Spirulina platensis with high proteins formed 34% N-containing compounds. Nannochloropsis sp. (high lipids) yielded 52% carboxylic acids and aliphatics. The lower heating value (LHV) of gas products was over 21 MJ/Nm 3 .